2010
DOI: 10.1111/j.1471-4159.2010.06769.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyrk1A‐mediated phosphorylation of Presenilin 1: a functional link between Down syndrome and Alzheimer’s disease

Abstract: The dual-specificity tyrosine(Y)-phosphorylation-regulated kinase 1A (Dyrk1A) gene is located on human chromosome 21 and encodes a proline-directed protein kinase that might be responsible for mental retardation and early onset of Alzheimer's disease (AD) in Down syndrome (DS) patients. Presenilin 1 (PS1) is a key component of the c-secretase complex in the generation of b-amyloid (Ab), an important trigger protein in the pathogenesis of AD. Increased Dyrk1A expression has been reported in human AD and DS brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…Given the paucity of selective DYRK1A inhibitors available, with the notable exception of harmine [25], advantage could be taken of dNBC to develop new selective inhibitors of this kinase, which plays important roles in neurodegenerative diseases [37]. For the time being, it should be born in mind that, in addition to DYRK1A, dNBC also drastically inhibits ERK8 and GSK3b, exhibiting an overall promiscuity higher than that of NBC, which is reflected in a Gini coefficient of 0.421 as compared to 0.568 for NBC (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given the paucity of selective DYRK1A inhibitors available, with the notable exception of harmine [25], advantage could be taken of dNBC to develop new selective inhibitors of this kinase, which plays important roles in neurodegenerative diseases [37]. For the time being, it should be born in mind that, in addition to DYRK1A, dNBC also drastically inhibits ERK8 and GSK3b, exhibiting an overall promiscuity higher than that of NBC, which is reflected in a Gini coefficient of 0.421 as compared to 0.568 for NBC (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 phosphorylation is regulated by SHP2, a tyrosine phosphatase activated by tyrosine residue phosphorylation [19]. DYRK1A is located in the DS critical region of HSA21 and belongs to the evolutionarily conserved dual-specificity tyrosine-(Y)-phosphorylation regulated kinase (DYRK) family [20]. Wiechmann et al [21] demonstrated that DYRK1A can phosphorylate Ser727 of STAT3 to increase its activity in COS cells.…”
Section: Introductionmentioning
confidence: 98%
“…43 Furthermore, DYRK1A also phosphorylates presenilin 1 (PS1), a subunit of γ-secretase, and this phosphorylation event increases γ-secretase protease activity, further elevating Aβ peptide production. 44 Moreover, research suggests a positive feedback mechanism through which Aβ stimulates the expression of DYRK1A, thereby further accelerating the synthesis of neurotoxic Aβ peptides. 45 These combined observations implicate DYRK1A intimately in the generation of both amyloid and tau pathologies associated with DS and AD and suggest the possibility that efficient pharmacologic inhibition of DYRK1A activity may help to ameliorate simultaneously the production of both pathologies.…”
mentioning
confidence: 99%